Budaya Algoritmik: Bagaimana AI Membentuk Identitas Manusia dan Norma Sosial - Djufri, Djufri (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
In the digital age, artificial intelligence (AI) has become a major force in shaping user experiences and social interactions in cyberspace. AI algorithms used in various digital platforms adjust content based on individual preferences, which indirectly shapes social identities and social norms within online communities. This research aims to examine how AI affects user interaction patterns, forms social identities, and strengthens or weakens social dynamics through mechanisms such as echo chambers and filter bubbles. This study uses a qualitative approach with an exploratory method, which involves semi-structured interviews with 20-30 participants from various backgrounds, as well as a quantitative survey of 300-500 respondents. The results show that AI plays a dual role in shaping social attachment, where 78% of respondents feel more connected to their digital community, but at the same time experience limited access to different perspectives due to algorithm personalization. Other findings suggest that AI algorithms contribute to increased social polarization by reinforcing boundaries between groups that have different views. In conclusion, while AI has the potential to create a more inclusive digital space, current algorithm implementations are more focused on extreme personalization, which narrows the openness to other perspectives. Therefore, more inclusive regulations and digital literacy education are needed so that users can be more critical of the information consumed and not be trapped in a narrow information cycle.